PENGARUH GOOD CORPORATE GOVERNANCE DAN MANAJEMEN LABA TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2013-2016 - Widya Pratiwi; Kamaliah Kamaliah; Al Azhar L (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
Financial performance is an achievement assessment of a company that can be seen from the ability owned by the company to earn profit. The company's profit aside from being an indicator of the company's ability to fulfill its obligations to investors is also an important element to support the prospects of the company in the future. One of the factors that influence the value of the company is financial performance. The purpose of this study is to determine the influence of the board of directors on financial performance, to determine the influence of the board of commissioners on financial performance, to determine the effect of managerial ownership on financial performance, and to determine the effect of earnings management on financial performance at banking companies listed on the Stock Exchange Indonesia in 2013-2016. The population used in this study are all banks listed in the Indonesia Stock Exchange period 2013-2016 which amounted to 42 banks and obtained a sample of 29 banks that meet the criteria. Analysis of research data using quantitative descriptive statistics with multiple linear regression approach. The result of the research concludes that the Board of Directors has positive and significant impact on the financial performance of banking listed in BEI period 2013-2016. Independent Board of Commissioners has a positive and significant impact on the financial performance of banks listed on the IDX period 2013-2016. Managerial ownership has a negative and insignificant effect on the financial performance of banks listed on the IDX period 2013-2016. Earnings Management has a negative and insignificant effect on the financial performance of banks listed in IDX for the period of 2013-2016.Keywords : Good Corporate Governance, Board of Directors, Independent Board of Commissioners, Managerial Ownership, Profit Management, Financial Performance